2021
DOI: 10.3389/fdgth.2021.610006
|View full text |Cite
|
Sign up to set email alerts
|

Remote Digital Measurement of Facial and Vocal Markers of Major Depressive Disorder Severity and Treatment Response: A Pilot Study

Abstract: Objectives: Multiple machine learning-based visual and auditory digital markers have demonstrated associations between major depressive disorder (MDD) status and severity. The current study examines if such measurements can quantify response to antidepressant treatment (ADT) with selective serotonin reuptake inhibitors (SSRIs) and serotonin–norepinephrine uptake inhibitors (SNRIs).Methods: Visual and auditory markers were acquired through an automated smartphone task that measures facial, vocal, and head movem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…We found no evidence of associations between pause rate and depressive symptoms in any speech tasks or language, in contrast to previous ndings. [6][7][8][9][10] This discrepancy may be due to the statistics (we took account of clustering of repeated measures within individuals) and none of the other studies were conducted in real world settings, meaning the speech collected could also be subject to the observer paradox (27). This is a phenomenon in which the speaking style of a participant changes due to the presence of a researcher or clinician during the recording session.…”
Section: Discussionmentioning
confidence: 99%
“…We found no evidence of associations between pause rate and depressive symptoms in any speech tasks or language, in contrast to previous ndings. [6][7][8][9][10] This discrepancy may be due to the statistics (we took account of clustering of repeated measures within individuals) and none of the other studies were conducted in real world settings, meaning the speech collected could also be subject to the observer paradox (27). This is a phenomenon in which the speaking style of a participant changes due to the presence of a researcher or clinician during the recording session.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, research effort has been dedicated to using computer vision and voice to directly quantify motor activity. Some recent work has demonstrated that digital phenotyping parameters that reflect gross motor activity including speech characteristics (rate of speech, tone) and facial/head movements are associated with suicidal risk, 189 SSRI response in MDD, 251 negative symptomatology in schizophrenia, 191 and Parkinsonian tremor. 252 Such approaches are now being commercialized for all phases of drug development from proof of concept to direct measurement in order to make decisions about ongoing treatment needs.…”
Section: Ml-powered Technologies For Psychiatrymentioning
confidence: 99%
“…As an example, research effort has been dedicated to using computer vision and voice to directly quantify motor activity. Some recent work has demonstrated that digital phenotyping parameters that reflect gross motor activity including speech characteristics (rate of speech, tone) and facial/head movements are associated with suicidal risk [241], SSRI response in major depressive disorder [242], negative symptomatology in schizophrenia [243], and Parkinsonian tremor [244]. Such approaches are now being commercialized for all phases of drug development from proof-ofconcept to direct measurement to make decisions about ongoing treatment needs.…”
Section: Commercial and Research Platforms And Servicesmentioning
confidence: 99%